THE ROLE OF SELF-REGULATED LEARNING IN MEDIATING THE EFFECT OF PERFORMANCE EXPECTANCY, EFFORT EXPECTANCY, FACILITATING CONDITIONS, AND SOCIAL INFLUENCE ON TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLEDGE (TPACK) COMPETENCE AMONG EDUCATION STUDENTS AT UNIVERSIT - Rohadi Kurniawan; Durinda Purpasari; Durinta Puspasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Digital transformation has required pre-service teachers to possess Technological Pedagogical Content Knowledge (TPACK) to effectively integrate technology, pedagogy, and subject matter in the learning process. This study aims to examine the effects of Performance Expectancy, Effort Expectancy, Facilitating Conditions, and Social Influence on TPACK and Self-Regulated Learning (SRL), as well as to investigate the mediating role of SRL among students of the Office Administration Education Study Program at Universitas Negeri Surabaya. This research employed a quantitative approach with a causal-associative research design. The Research population consist of 187 and research samples amounted to 126 students were selected using the proportional random sampling technique. Data were collected through a Likert-scale questionnaire and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS software. The findings revealed that Performance Expectancy, Facilitating Conditions, and Social Influence had a positive and significant effect on SRL, whereas Effort Expectancy had no significant effect. Furthermore, all four independent variables, as well as SRL, showed no significant direct effect on TPACK. The mediation analysis also indicated that SRL did not mediate the relationships between Performance Expectancy, Effort Expectancy, Facilitating Conditions, Social Influence, and TPACK. These findings suggest that improving TPACK requires additional supporting factors beyond technology acceptance and self-regulated learning, such as digital literacy, teaching practicum experience, and pedagogical competence. Future studies are recommended to incorporate additional variables and involve broader research settings across different study programs to develop a more comprehensive research model.